A method for the assessment of facial hedonic reactions in newborns - Caroline Ayres; Charles F. Ferreira; Juliana R. Bernardi; Thiago B. Marcelino; Vânia N. Hirakata; Clécio H. da Silva; Marcelo Z. Goldani (Jornal de Pediatria)
Abstract Objective: This study describes a quantitative and qualitative methodology to assess hedonic responses to sweet stimulus in healthy newborns. Methods: A descriptive, cross-sectional, observational study, with healthy newborns (up to 24 h of life), between 37 and 42 gestational weeks, vaginally born and breastfed previously to all tests. The evaluation of the newborns reactions was performed by hedonic facial expression analysis, characterized by facial expressions with rhythmic serial tongue protrusion after neutral or sweet solution intake. Initially, 1 mL of water solution was provided to the newborn, followed by a 1-minute recording. Afterwards, the same amount of 25% sucrose solution was provided, performing a second recording. The concordance between researchers was analyzed by the Bland-Altman statistical method. Results: A total of 100 newborns (n = 49 males, n = 51 females; mean lifetime = 15 h 12 min ± 6 h 29 min) were recorded for neutral and sucrose solution intake, totaling 197 videos (n = 3 missing in the water treatment). These videos were double-blind analyzed and the test revealed a 90% concordance between the two trained researchers, in relation to both solutions. The intraclass correlation coefficient was 0.99 for both solutions, with a significant increase in frequency of hedonic expressions evoked by sucrose solution intake. Conclusions: These results confirm that the proposed method has an efficient power to detect significant differences between neutral and sucrose stimuli. In conclusion, this evaluation method of hedonic facial reactions in newborns reflects the response to a specific taste.